THE INFLUENCE OF ISLAMIC LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEES PERFORMANCE OF AGENCY SHARIAH FINANCE - Efrina, Lisa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Competition in the increasingly fierce of globalization era requires agencies or companies to continue to improve their performance in improving the performance of their employees by creating a pleasant and equal work environment between members of the organization. This research aims to examine the influence of Islamic leadership and organizational culture on employee performance. This research was conducted at sharia multi-finance company. The sampling method in this research is the saturated method. sampling of 35 respondents. Data analysis used the SPSS program with multiple regression analysis. The research results show that Islamic leadership has a positive influence on employee performance. What leaders do becomes an example and model for their subordinates. Leadership also requires the totality of its subordinates to work optimally to support maximum performance improvement. Leaders have also shown the same attitudes, thoughts and work patterns, while the organizational culture has not. affect employee performance. because the indication is that every employee is still guided by the old culture without disrupting performance. Furthermore, Islamic leadership and organizational culture variables simultaneously have a positive effect on employee performance. This variable does have a strong relationship. Organizational culture will not be created without a leader who is of course followed by organizational members.